mRNA-1273 vaccination induces polyfunctional memory CD4 and CD8 T cell responses in patients with solid cancers undergoing immunotherapy or/and chemotherapy - Gangaev, Anastasia; van Sleen, Yannick; Brandhorst, Nicole; Hoefakker, Kelly; Prajapati, Bimal; Singh, Amrita; Boerma, Annemarie; van der Heiden, Marieke; Oosting, Sjoukje F.; van der Veldt, Astrid A. M.; Hiltermann, T. Jeroen N.; GeurtsvanKessel, Corine H.; et al. (Frontiers in Immunology, 2024)
Introduction Research has confirmed the safety and comparable seroconversion rates following SARS-CoV-2 vaccination in patients with solid cancers. However, the impact of cancer treatment on vaccine-induced T cell responses remains poorly understood. Methods In this study, we expand on previous findings within the VOICE trial by evaluating the functional and phenotypic composition of mRNA-1273-induced T cell responses in patients with solid tumors undergoing immunotherapy, chemotherapy, or both, compared to individuals without cancer. We conducted an ELISpot analysis on 386 participants to assess spike-specific T cell responses 28 days after full vaccination. Further in-depth characterization of using flow cytometry was performed on a subset of 63 participants to analyze the functional phenotype and differentiation state of spike-specific T cell responses. Results ELISpot analysis showed robust induction of spike-specific T cell responses across all treatment groups, with response rates ranging from 75% to 80%. Flow cytometry analysis revealed a distinctive cytokine production pattern across cohorts, with CD4 T cells producing IFNγ, TNF, and IL-2, and CD8 T cells producing IFNγ, TNF, and CCL4. Variations were observed in the proportion of monofunctional CD4 T cells producing TNF, particularly higher in individuals without cancer and patients treated with chemotherapy alone, while those treated with immunotherapy or chemoimmunotherapy predominantly produced IFNγ. Despite these differences, polyfunctional spike-specific memory CD4 and CD8 T cell responses were comparable across cohorts. Notably, immunotherapy-treated patients exhibited an expansion of spike-specific CD4 T cells with a terminally differentiated effector memory phenotype. Discussion These findings demonstrate that systemic treatment in patients with solid tumors does not compromise the quality of polyfunctional mRNA-1273-induced T cell responses. This underscores the importance of COVID-19 vaccination in patients with solid cancers undergoing systemic treatment.